Students’ narratives on gender and sexuality in the project of social justice and belonging in higher education - Ngabaza, S.; Shefer, T.; Clowes, L. (South African Journal of Higher Education, 2018)
Student protests in South Africa flag the well-documented lack of progress in transforming universities which mirror deeply entrenched inequalities. The imperative to challenge a system of higher education that continues to rationalise and reproduce injustice is even more keenly felt. Efforts to understand the lived experiences of young people within diverse higher educational contexts are arguably especially important in this context. This paper draws on research with students at the University of the Western Cape (UWC) who engaged in a participatory photovoice research project in a feminist research methodology module. Students were asked to take photos on and around campus that represented un/safe spaces for them and to write short narratives on these. The paper unpacks key emerging themes that speak to how gender, intersecting with sexuality, informs experiences of belonging, while arguing the value of student voice in the project of social justice in higher education.